Comparison of Thermal Insulation Concrete Panel Yield Based on Natural Fibres: A Review - Rosli, Norsyaza Aqilah; Abdul Rahman, Mohd Fahmi (Journal of Advanced Industrial Technology and Application, 2021)
Over time, many researchers have conducted studies to investigate the construction sector by assessing those related to energy, environmental and economic problems to find ways to improve global sustainability. The studies on the use of natural fibers: wheat, date palm and hemp as an insulating material in concrete panel yields have been conducted through ten previous research studies. In the market, there are various types of thermal insulation materials but these materials are sold at high prices and even worse some of them contain harmful chemicals that can threaten the health of consumers. This study is intended to identify ten previous research studies on the use of natural fibers in concrete panel yield as thermal insulation materials. Also, to analyse the data of density and coefficient of thermal conductivity accumulated through Microsoft Excel and propose the best concrete panels yield between these three types of natural fibers. The research was based on the value of density and coefficient of thermal conductivity of concrete panel yield. The results reveal that the presence of natural fibers in concrete panels can insulate heat well. The lowest thermal conductivity coefficient obtained from concrete of Hemp Fibre Gypsum (HG) with 0.051 W/mK. The composition of 35g of hemp fiber, 200g of gypsum and 130ml of water has shown that the amount of fibre and binder used plays an important role in determining the value of density and thermal conductivity. Finally, based on the analysis that has been conducted, found that density and thermal conductivity are inversely proportional when there is a change in the composition of fibers and binders in the concrete panel yields.